2018
DOI: 10.1155/2018/1436521
|View full text |Cite
|
Sign up to set email alerts
|

Application of Finite Mixture of Logistic Regression for Heterogeneous Merging Behavior Analysis

Abstract: A finite mixture of logistic regression model (FMLR) was applied to analyze the heterogeneity within the merging driver population. This model can automatically provide useful hidden information about the characteristics of the driver population. EM algorithm and Newton-Raphson algorithm were used to estimate the parameters. To accomplish the objective of this study, the FMLR model was applied to a trajectory dataset extracted from the NGSIM dataset and a 2-component FMLR model was identified. The important fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…If the value of hypothesis hθ(w) ≥ 0.5, then it shows that z = 1 implying that the person has Cardiovascular disease and if hθ(w) < 0.5, then z = 0 implying that the person is healthy. Therefore, under the condition 0 ≤ hθ(w) ≤ 1, the prediction of Logistic Regression is done [30]. The Logistic Regression function is expressed as:…”
Section: A Logistic Regressionmentioning
confidence: 99%
“…If the value of hypothesis hθ(w) ≥ 0.5, then it shows that z = 1 implying that the person has Cardiovascular disease and if hθ(w) < 0.5, then z = 0 implying that the person is healthy. Therefore, under the condition 0 ≤ hθ(w) ≤ 1, the prediction of Logistic Regression is done [30]. The Logistic Regression function is expressed as:…”
Section: A Logistic Regressionmentioning
confidence: 99%
“…For details on the data processing, one can refer to Ref. [5], [6], [66] After smoothing, filtering and consistency checking, trajectories of 388 merging vehicles were extracted from the dataset.…”
Section: B Data Processingmentioning
confidence: 99%
“…In previous studies, drivers are always assumed to be homogeneous and consistent during the driving process, which raises questions regarding the performance of microscopic traffic simulation models in representing reality [9]- [14]. Studies have demonstrated wide heterogeneity among drivers in terms of driving behavior [5], [6], [15], [16]. Different drivers may behave differently under the same traffic conditions and the same driver may even behave differently under varying traffic conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the vicinity of these bottlenecks, the lane-changing behavior is shown to affect traffic throughput, safety, and turbulence (6)(7)(8)(9)(10)(11)(12). A limited body of research has shown that heterogeneity exists within the merging and diverging behaviors of drivers (13)(14)(15). However, they do not take into account the behavior of truck drivers who are a significant part of traffic on truck-dominated motorways.…”
mentioning
confidence: 99%